Authorization delegation mechanism based trust level in grid computing - DENG Yong1; CHEN Jian-gang 1; WANG Ru-chuan1; ZHANG Lin1 (Tongxin xuebao)
To meet the demand of the delegation service during multi-domain authorization in grid computing,the dele-gation negotiation process is presented to realize the authorization delegation of role and permission based on the RBDM and RT model through the introduction of trust levels.The fine-grain authorization delegation policy is given.Finally,the simulation is given to prove the feasibility of the delegation model with trust level.